Answers

2014-06-15T12:07:19+08:00
(2x+y+3z)^2

(2x+y+3z) times (2x+y+3z)

2x is the first term
y is the second term
3z is the third term

You need to multiply the first term to first term
next first to second
first to third
--
2x times 2x = 4x^2 
2x times y= 2xy
2x times 3z= 6xz
this is the first batch 4x^2+ 2xy+6xz
--
next is Second term to first term
second to second
second to third.
--
y times 2x = 2xy
y times y= y^2
y times 3z= 3yz
the seond batch of equation is 2xy+y^2+3yz
--
Then, the third term to first
third to second
third to third.
--
3z times 2x =6xz
3z times y= 3yz
3z times 3z= 9z^2
--
thas is the last batch 6xz +3yz+9z^2
--
Thats like destributive property :)
Now combine like terns,

--
4x^2+ 2xy+6xz
2xy+y^2+3yz
6xz +3yz+9z^2
 the answer is 
--
4x^2+4xy+12xz+y^2+6yz+9z^2
--
The same process with the next one. Hope it helps
0
is that the square of trinomial?
Yes.